PENGARUH PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN KEAKTIFAN BERORGANISASI TERHADAP KESADARAN MODERASI BERAGAMA SISWA DI SMK NEGERI 2 PEKANBARU - Eko Wibowo (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2023)
This study aims to determine the effect of learning Islamic religious education and activeness in organizations on students' awareness of religious moderation at SMK Negeri 2 Pekanbaru. This research is a field research with a quantitative approach. The research sample was 341 students at SMK Negeri 2 Pekanbaru. Data collection techniques using questionnaires, observation, interviews and documentation. Data analysis techniques using linear and multiple regression. The results of this study indicate that the learning of Islamic religious education has no significant effect on students' awareness of religious moderation at SMK Negeri 2 Pekanbaru. This is indicated by the results of r count which is smaller than r table (0.024 <0.113), and its significance value is 0.662 > 0.005, contributing only 00.1%. Organized activity does not have a significant effect on students' awareness of religious moderation at SMK Negeri 2 Pekanbaru. This is indicated by the results of r count which is smaller than r table (0.030 <0.159), and its significance value is 0.586 > 0.005, contributing only 00.1%. There is no significant effect of Islamic religious education learning and organizational activity on students' awareness of religious moderation at SMK Negeri 2 Pekanbaru. This is indicated by F count < F table (0.253 < 3.04), and a significance value of 0.776 > 0.005, contributing only 00.1%. This means that the contribution of the independent variable to the dependent variable is 00.1%.